Interrelationships between students' anxiety toward mathematics, students' beliefs toward mathematics, mathematics performance and confidence in solving mathematical problems - Christine, Wong Ing Ming (Universiti Malaysia Sarawak (UNIMAS), 2009)
This research investigated the interrelationships between students' anxiety toward mathematics, students' beliefs toward mathematics, mathematics performance and confidence in solving mathematical problems among Form Four students. One hundred sixty students from four secondary schools were selected as the samples of this study. Research instruments consisting of rMARS, Students' Beliefs Toward Mathematics survey form, and some mathematics tests were used to measure students' anxiety toward mathematics, students' beliefs toward mathematics, mathematics performance and confidence in solving mathematical problems respectively. Pearson-product moment correlations were used to measure the relationship between students' anxiety toward mathematics and mathematics performance, relationship between students' anxiety toward mathematics and confidence in solving mathematical problems, relationship between students' beliefs toward mathematics and mathematics performance, relationship between students' beliefs toward mathematics and confidence in solving mathematical problems, and relationship between mathematics performance and confidence in solving mathematical problems. Independent ttests and One-Way ANOVA were used to measure the differences in students' anxiety toward mathematics, students' beliefs toward mathematics, mathematics performance and confidence in solving mathematical problems based on gender, race, PMR mathematics grades, students attending mathematics tuition and assistance in doing mathematics homework respectively. The results showed negative relationship between students' anxiety toward mathematics and mathematics performance, negative relationship between students' anxiety toward mathematics and confidence in solving mathematical problems. There were however positive relationship between students' beliefs toward mathematics and mathematics performance, positive relationship between students' beliefs toward mathematics and confidence in solving mathematical problems, and positive relationship between mathematics performance and confidence in solving mathematical problems. No significant differences in students' anxiety toward mathematics, mathematics performance and confidence in solving mathematical problems were found based on gender, students attending mathematics tuition, and assistance in doing mathematics homework. Significant differences were detected based on race and PMR mathematics grades. The result also showed no significant differences in students' beliefs toward mathematics based on gender, race, PMR mathematics grades, students attending mathematics and assistance in doing mathematics homework